Distal acquired demyelinating symmetric (DADS) neuropathy associated with colorectal adenocarcinoma. Issue 6 (24th April 2015) - Ayyappan, Sujith; Day, Timothy; Kiers, Lynette
ABSTRACT Introduction Paraneoplastic neuropathies are well recognized as a remote effect of cancer, and subacute sensory neuronopathy is a recognized syndrome. Demyelinating neuropathies are relatively rare. Distal acquired demyelinating symmetric (DADS) neuropathy associated with lymphoproliferative disease has been reported previously. We present the association of DADS neuropathy with solid tumor. Methods We report the clinical presentation, electrophysiology, and progress of DADS neuropathy in a patient later found to have colorectal adenocarcinoma. Results A patient presented with subacute onset of symmetric distal sensory and motor symptoms. Electrophysiology was typical of DADS neuropathy. Anti‐MAG antibodies were initially positive at low titer, and indirect immunofluorescence analysis for anti‐nuclear antibodies revealed autoantibodies to centromere nuclear protein‐F (CENP‐F). There was clinical and electrophysiologic resolution after tumor resection. Conclusions This case describes the presentation of DADS neuropathy as a paraneoplastic syndrome in a patient later found to have colorectal adenocarcinoma. Muscle Nerve51: 928–931, 2015